METODE PENDIDIKAN DALAM PEMBENTUKAN MENTAL ANAK DI YAYASAN PEMBINAAN ANAK CACAT JALAN ADI NEGORO NO. 02 MEDAN - Zulkarnaen Guchi, Nisa Aulia Butar Butar, Abdul Rahman Sofyan, (Fakultas Agama Islam, 2022)
The purpose of the study was to find out the learning system or method used at the Medan Disabled Children Development Foundation so that students understand the learning materials used in the learning process. The research used a descriptive qualitative method. Data collected through observation and interviews as well as documentation. Research conducted by researchers proves that the learning method used is successful in educating children with special needs. The focus of this research are: (1) How is the method of education in the mental formation of children. (2) What are the factors that influence the method of education in the mental formation of children at the Adi Negoro Street Children's Development Foundation in Medan. (3) What are the efforts made by teachers in the mental formation of children at the Jalan Adi Negoro Foundation for Children with Disabilities No. 02 Medan. The result of this study is that learning is more directed to teachers who must be able to understand the character of students and what learning methods can be used in the learning process. Because in the learning process that takes place the teacher must be able to master all existing learning methods. It could be that there are 5 children in the class, then 5 learning methods are used. The results showed that all methods in the learning process at SLB YPAC were the same as in public schools using the following methods: Lectures, Discussions, Questions and Answers, Demonstration, and Experiments. However, there is one main learning method used in the learning process at SLB YPAC, namely Problem Baset Learning.